Fipronil na bioenergética de mitocôndrias isoladas de figado de rato - Palma, Ivo Dias Ferreira da [UNESP] (2014)
Fipronil is a highly effective insecticide and acaricide that belongs to the phenylpyrazole chemical family and it has been extensively used to control fleas, ticks and lice of dogs, cats and bovines.As reported by literature, there are intoxication cases due to the accidental exposure or mistaken fipronil application in mammals, it might affect including the liver that performs essencial functions related to metabolism, due to the liver receives nutrients and xenobiotics that are absorbed, converted, stored and released into the blood. The mitochondria is responsible for almost entirety ATP synthase required to maintaining cellular structure and function. In this paper were evaluated the fipronil effects on bioenergetic of isolated rat-liver mitochondria. In the tested concentrations (5 to 25 μM), the fipronil inhibited State III of respiration to mitochondria energized with glutamate + malate, complex I substrates of respiratory chain, besides dissipate mitochondrial membrane potential, resulting in mitochondrial ATP synthase inhibition. The fipronil inhibitor effect about the complex I was confirmed by the inhibiting enzyme NADH dehydrogenase activity. The effect presented by fipronil about the mitochondrial bioenergetic may be related to the toxic effect showed by the insecticide on liver